Humaniza redes: combate ao hate speech e a concretização da liberdade de expressão como um direito humano ao desenvolvimento - Bem, Vyrna Lopes Torres de Farias (2018)
The will to be free changed society in the sense that it was the first right to be demanded by the citizens, when they rebelled against the absolutism of the State. After the right to freedom was defined as a fundamental human right, other forms of freedom were born, one of which was related to communication. Throughout history, communication has always been considered an instrument of manifestation of thought and opinion, however, nowadays, it has been transformed by the internet. Specifically, social networks are changing the scenario regarding freedom of speech. These technological tools made the discourse enter a creative, dynamic and immediate world. The evolution of this means of communication is raising an important question about the manifestation of thought and the violation of the personality rights. In many cases, this freedom of speech becomes a manifestation of racism, concretizing the hate speech. For this reason, the issue should be analyzed, especially when there is a public policy to resolve the problem. In this way, it is necessary to seek legal mechanisms to make compatible the various virtual manifestations, published in social networks, with the protection of the personality rights. The aim is to combat the hate speech by helping the institute known as humaniza redes and civil liability law, as a way of guaranteeing the human right to development. This dissertation aims to discuss the limits of freedom of speech, without ruling out this fundamental right.